1997
DOI: 10.1021/ja964345m
|View full text |Cite
|
Sign up to set email alerts
|

From Monomers to π-Stacks. A Comprehensive Study of the Structure and Properties of Monomeric, π-Dimerized, and π-Stacked Forms of the Cation Radical of 3‘,4‘-Dibutyl-2,5‘‘-diphenyl-2,2‘:5‘,2‘‘-terthiophene

Abstract: 3‘,4‘-Dibutyl-5,5‘‘-diphenyl-2,2‘:5‘,2‘‘-terthiophene (Bu2Ph2Tth) can be readily converted to the stable cation radical [Bu2Ph2Tth]+. The hexafluorophosphate salts of the cation radical ([Bu2Ph2Tth]PF6) are synthesized in millimolar quantities by either chemical or constant current electrochemical oxidation; the latter method gave X-ray quality single crystals. X-ray powder diffraction studies indicate the materials from both syntheses have the same structure. The crystal structure of [Bu2Ph2Tth]PF6 was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
105
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(120 citation statements)
references
References 45 publications
14
105
0
1
Order By: Relevance
“…The isosbestic point around 400-450 nm indicates the interconversion of two species, consistent with the oxidation of TIPS-Tn-TIPS into [TIPS-Tn-TIPS]C + . The appearance of two low-energy spectral features associated with the formation of the radical cation is in agreement with the numerous spectroelectrochemical [19][20][21][22][23][24][25][26][27][28][29][30][31] and quantum-chemical [32][33][34][35][36][37][38] studies reported for a great variety of a-oligothiophenes. The in situ UV/Vis/NIR spectra were recorded at room temperature and for low TIPS-Tn-TIPS concentrations, and, therefore, show no indication of the for- Figure 9.…”
Section: Optical Properties Of Oxidized Tips-tn-tips Oligothieno-a C supporting
confidence: 88%
See 1 more Smart Citation
“…The isosbestic point around 400-450 nm indicates the interconversion of two species, consistent with the oxidation of TIPS-Tn-TIPS into [TIPS-Tn-TIPS]C + . The appearance of two low-energy spectral features associated with the formation of the radical cation is in agreement with the numerous spectroelectrochemical [19][20][21][22][23][24][25][26][27][28][29][30][31] and quantum-chemical [32][33][34][35][36][37][38] studies reported for a great variety of a-oligothiophenes. The in situ UV/Vis/NIR spectra were recorded at room temperature and for low TIPS-Tn-TIPS concentrations, and, therefore, show no indication of the for- Figure 9.…”
Section: Optical Properties Of Oxidized Tips-tn-tips Oligothieno-a C supporting
confidence: 88%
“…[5,14] The charged species formed in the oxidation/reduction processes of a great variety of oligothiophenes have been monitored and characterized by using UV/Vis/NIR spectroelectrochemistry. [19][20][21][22][23][24][25][26][27][28][29][30][31] Quantum-chemical calculations have been shown to be very helpful in correctly assigning the optical absorptions of the charged species, and in corroborating the nature of these species (radical cations, dications, and radical cation p-dimers). [32][33][34][35][36][37][38] Therefore, the combination of spectroelectrochemistry and quantum-chemical calculations provides an efficient tool for the investigation of the charged species involved in the charge transport process in p-conjugated oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…However, crystalline samples of oligothiophene radicalc ations with a pdimers tructure are rare. [39][40][41] This lack of pure samples with structurali nformationh as hampered detailed investigations of the magnetic properties of the p-dimers.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] In particular, p dimers of oligothiophene radical cations were proposed two decades ago to play a key role in electronic conduction of p-doped polythiophenes. [24] Investigations into the mechanism of the interaction between oligothiophene radical cations [1][2][3][4][5][6][7][8][25][26][27][28][29][30] deepen the understanding of the chemistry of this particularly attractive building block for organic electronics. For instance, it has been found that the tendency for intermolecular p dimerization can be attenuated and, in some cases, shut down when bulky groups are inserted in the b positions at thiophene rings; [31][32][33][34] note the evidence from X-ray crystallography that the closest intermolecular contact in the p dimer of nonhindered systems takes place at the central rings.…”
Section: Introductionmentioning
confidence: 99%